Conventional Approach for Fabrication of Orbital Prosthesis: A Case Report - Singh, Tanuja; Mathema, Suraj Ram Bhakta; Manandhar, Pratik (Birat Journal of Health Sciences, 2018)
Facial defect rehabilitation is a very critical task which requires personalized design of the prosthesis for each patient. Eyes are vital organ not only for vision but also for the facial expression. Disfigurement due to loss of an eye and associated structures may cause physical and psychological distress to the patient. Rehabilitating such patient with a removable orbital prosthesis is an economical and patient-friendly procedure which restores the patient's social as well as the cosmetic value. The present article describes a conventional technique for the fabrication of a spectacle retained acrylic resin orbital prosthesis providing accurate and effective rehabilitation. BJHS 2018;3(2)6:495-499.